Prospective Belgian study of neurodegenerative and vascular dementia: APOE genotype effects. Issue 8 (21st July 2003) - Engelborghs, S; Dermaut, B; Goeman, J; Saerens, J; Mariën, P; Pickut, BA; Van den Broeck, M; Serneels, S; Cruts, M; Van Broeckhoven, C; De Deyn, P P
Abstract : Objective: The authors conducted a prospective study of neurodegenerative and vascular dementia in Belgium. Strict diagnostic inclusion criteria were used to include well defined patients and controls. The results of apolipoprotein E (APOE) genotype effect on risk and clinical characteristics are presented. Methods: APOE genotyping was performed in patients with probable Alzheimer's disease (AD) (n=504), frontotemporal dementia (FTD) (n=47), vascular dementia (VaD) (n=152), mixed dementia (n=132), mild cognitive impairment (MCI) (n=44), Parkinson's disease (PD) (n=30), dementia with Lewy bodies (DLB) (n=17), and multisystem atrophy (MSA)/progressive supranuclear palsy (PSP) (n=12). Results: The APOE allele frequencies of this Belgian control population (ε2: 6.9%; ε3: 76.2%; ε4: 16.9%) did not differ from those reported for other white populations. AD, MCI, and mixed dementia patients had higher APOE ε4 (32.9%, 38.6%, and 28.4% respectively) and lower APOE ε3 (62.2%, 53.4%, and 66.3%) frequencies compared with controls, whereas only AD and mixed dementia patients had lower APOE ε2 frequencies (4.9% and 5.3%). Apart from a borderline significant different distribution of APOE allele frequencies in VaD patients compared with controls, no other differences were detected. The influence of APOE ε4 on clinical features of dementia was limited to lower age at onset in AD patients and a less pronounced negative correlation between age at onset and number of ε4 alleles in MCI and mixed dementia patients. Conclusions: This study confirmed the risk association between APOE ε4 and AD. The observation that APOE ε4 is associated with mixed dementia reflected the role of AD in the aetiopathogenesis of this condition. Although MCI is an aetiologically heterogeneous syndrome, the increased APOE ε4 frequencies indicated that a large proportion of the MCI patients included in the study might be predisposed to develop AD.